Comparison of standard diagnostic and radiotherapy planning protocols in lung cancer treatment on PET/ CT scanner - Vlaj, Filip (Medical imaging and radiotherapy journal, 2020)
Purpose: The purpose of the study was to compare the standard diagnostic protocol for computed tomography imaging with a radiotherapy imaging protocol for treatment planning needs in radiotherapy for lung cancer on a positron emission tomography (PET/CT) scanner at the Department of Nuclear Medicine in order to then be able to determine the diff erences between these two protocols and suggest improvements in dose optimisation for computed tomography imaging in a radiotherapy protocol. Methods: In a retrospective study, data were collected with the SyngoVia program and statistically analysed according to the patient dose load in computed tomography imaging in standard PET /CT and radiotherapy protocols. The analysis included data of 56 patients for the period from 1 January 2017 to 1 December 2018. We compared data on patient dose load in computed tomography imaging in a standard protocol before and after introducing the improved sinogram-affi rmed iterative reconstruction method (SAFIRE). Results and discussion: Statistically signifi cant diff erences in dose per patient (p<10 -3 ) in computed tomography imaging in standard PET/CT and radiotherapy protocols on PET/CT scanner were found. Statistically signifi cant diff erences were also established in computed tomography imaging in the standard PET/CT protocol before and after the introduction of the improved iterative reconstruction method (p=0.001). Dose load on the lung in computed tomography imaging was 67.5% lower in the standard protocol with the iterative reconstruction in image space (IRIS) method than in the radiotherapy protocol. The introduction of the improved SAFIRE method additionally lowered the dose per patient by 34.2% compared to the IRIS method. Conclusion: In the future, the improved iterative reconstruction method should be introduced for the reconstruction of computed tomography images for radiotherapy imaging protocol in lung cancer . The impact of the indirect reduction in the dose, which has an infl uence on the accuracy of the contouring of tumour target volumes for patient treatment planning, should be taken into account.
Keywords: dose optimization; iterative reconstruction; iterativna rekonstrukcija; optimizacija doze; positron emission tomography with computed tomography; pozitronska emisijska tomografija z računalniško tomografijo